Implementation of Educational Technology for teacher profession in Vocational High Schools - Aisyah Argyanti; Monica Fajriana; Linda Setiawati (Inovasi Kurikulum, 2023)
Educational technology is a field of science engaged in study and practice in facilitating learning, managing resources and processes, and improving performance. The profession and scope of work for educational technology graduates are wide and varied. Still, many educational technology graduates work in the education sector, especially as vocational high school teachers. Regarding this, of course, there is a lot of experience and knowledge related to educational technology that must be applied to the scope of learning. So, studies and research were designed regarding applying educational technology science to the teaching profession in vocational high schools. The analysis was carried out using a descriptive qualitative approach by collecting data through interviews with several graduates of educational technology who work as teachers in vocational high schools. Interviews were conducted to determine the challenges of educational technology graduates, the application of educational technology science, and the code of ethics in schools. The results obtained are that educational technology graduates have a strong foundation and study in managing and facilitating learning so that teachers of educational technology graduates can easily apply knowledge and a code of ethics within the scope of vocational high schools. It can be concluded that the application of educational technology science to the teaching profession in vocational high schools is well and optimally applied regarding the application of knowledge, the applicable code of ethics, and the constraints and challenges faced. AbstrakTeknologi pendidikan merupakan suatu bidang ilmu yang bergerak pada studi dan praktis dalam memfasilitasi pembelajaran, pengelolaan sumber dan proses, serta peningkatan kinerja. Profesi dan ruang lingkup pekerjaan lulusan teknologi pendidikan sangat luas dan beragam, tetapi tidak sedikit juga lulusan teknologi pendidikan yang bekerja pada bidang pendidikan, terutama sebagai guru sekolah menengah kejuruan. Berangkat dari hal tersebut, tentu banyak pengalaman dan ilmu terkait teknologi pendidikan yang harus diterapkan pada ruang lingkup pembelajaran. Maka, dirancanglah studi dan penelitian mengenai penerapan ilmu teknologi pendidikan pada profesi guru di sekolah menengah kejuruan. Adapun penelitian yang dilaksanakan menggunakan pendekatan kualitatif deskriptif dengan melakukan pengumpulan data melalui wawancara kepada beberapa lulusan teknologi pendidikan yang berprofesi sebagai guru di sekolah menengah kejuruan. Wawancara dilakukan untuk mengetahui apa saja tantangan lulusan teknologi pendidikan, penerapan ilmu teknologi pendidikan, dan kode etik yang diterapkan di sekolah. Hasil yang didapat yaitu lulusan teknologi pendidikan memiliki dasar dan studi yang kuat dalam mengelola dan memfasilitasi pembelajaran, sehingga pada guru lulusan teknologi pendidikan dapat dengan mudah menerapkan ilmu serta kode etik dalam ruang lingkup sekolah menengah kejuruan. Dapat disimpulkan bahwa penerapan ilmu teknologi pendidikan pada profesi guru di sekolah menengah kejuruan dapat diimplementasikan dengan baik dan optimal menyangkut penerapan ilmunya, kode etik yang berlaku, dan kendala serta tantangan yang dihadapi.Kata Kunci: Guru; profesi; Sekolah Menengah Kejuruan; teknologi pendidikan